1199 PREVENTION AND TREATMENT OF CRITICAL ILLNESS ACQUIRED WEAKNESS IN THE ELDERLY. (16th January 2023) - Costa, C; Moniati, F
Abstract: Introduction: Critical Illness Acquired weakness (ICU-Acquired Weakness (ICU-AW)) is an umbrella term used to describe Critical Illness Myopathy (CIM) and Critical Illness Polyneuropathy (CIP). The condition exerts high prevalence in the elderly admitted in the ICU and is associated with deteriorating patient outcomes, namely mortality and morbidity. The prevalence of the syndrome is highly variable in the current literature hindering our ability to objectively quantify the scale of the problem. Moreover, several preventative methods and treatment for ICU-AW as a result of sarcopenia have been proposed in literature with some of them providing favourable outcomes. Objectives: 1. Evaluate the prevalence of ICU-AW in the elderly through a systematic review; and 2. Explore the treatment options currently available. Methods: We conducted a systematic review using the PubMed, Embase and Cochrane databases to explore the current studies available on the diagnosis of ICU-AW syndromes. Cochrane's Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement was our template. Results: Overall, twenty-one studies (1544 patients) were included. The minimum reported prevalence is 20%, whereas the maximum is 76%. The overall median prevalence was 52% (Q1: 32% and Q3: 61%) with an interquartile range (IQR) of 29%. The highest IQR was found in studies using clinical examination (IQR=37%) whereas the lowest in studies using electrophysiological assessment (IQR= 21%). Moreover, several preventative measures for ICU-AW were identified and analyzed namely: nutritional alterations (high protein dies), glucose control, early mobilization, neuromuscular electrical stimulation and the ABCDEF bundle. Conclusion: The variability in the diagnostic modalities used to measure the syndrome as well as the inconsistency in the diagnostic parameters within each modality prevent us from objectively quantifying the prevalence of ICU-AW. With regards to treatment early mobilization protocols offer promising evidence. Reference: Vanhorebeek, Latronico, Van den Berghe G. ICU-acquired weakness. Intensive Care Med . 2020;46(4):637-53.